Evaluation/Impact Assessment of "Rural Sports Programme" Centre for Market Research and Social Development - Planning Commission (Planning Commission, 2001)
Over the years, the Government of India has launched several programmes to encourage sports ill the country. However, we are yet to achieve a place of pride in international sports. We are lagging much behind even among the Asian countries. This indicates that implementation of sports programmes in the country leaves for much space for progress. To promote sports in India, Govt of India issued a new National Sports Policy in 2001.
Planning Commission Government of India
Planning Commission Government of India